2002
DOI: 10.1080/00986440214059
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effects on Single Aqueous Drops Falling through an Immiscible Organic Liquid

Abstract: Drop settling (or rising) is crucial to the breaking of liquid-liquid dispersions. Most of the empirical correlations for terminal velocity of drops are formulated based on experimental data for systems of dispersed organic phase and continuous aqueous phase using pure and nearly pure liquids. Because the presence of the various third components in one or both of the phases may affect the settling of the drops, the terminal velocity and the onset of oscillation of aqueous drops containing various concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…As a result, increase of density difference becomes the major factor to influence terminal velocity. Therefore, terminal velocity increase obviously at high concentrations, which also accounts for the same trend in literature (Chen et al, 2010). But the difference is that the butanol/water system shows a very small variation at low concentration due to limit interfacial tension change.…”
Section: Influence Of Salt Concentrationsupporting
confidence: 83%
See 1 more Smart Citation
“…As a result, increase of density difference becomes the major factor to influence terminal velocity. Therefore, terminal velocity increase obviously at high concentrations, which also accounts for the same trend in literature (Chen et al, 2010). But the difference is that the butanol/water system shows a very small variation at low concentration due to limit interfacial tension change.…”
Section: Influence Of Salt Concentrationsupporting
confidence: 83%
“…His work revealed that a toluene drop was slowed down because the addition of salt. Also in toluene-water test system, Chen et al (Chen et al, 2010) found that the terminal velocity was increased as the salt concentration increased from 0.01M to 2M. Zameek et al (Zameek et al, 2016) derived the same trend as Chen et al, they studied the single crude oil drop rising in electrolytes with low, moderate and high concentration.…”
Section: Introductionmentioning
confidence: 71%